Analisis Permasalahan Sosial Teman Sebaya di Kalangan Siswa SMP: Studi Literatur - Adellia Ezadany; Indah Khomaria Suseno; Chotrun Nisa' Muhibaturrohmah; Anisa Dias Rofianty; Charisma Daniyah; Denok Setiawati; Mila Yunita (Yayasan Al-Afif, 2025)
Social problems among peers are common phenomena in junior high school students that may affect their social, emotional, and moral development. This study aims to analyze various forms of peer-related social problems such as conflicts, social exclusion, and peer pressure based on a literature review of 23 nationally accredited journals (Sinta 2–6). The research employed a systematic literature review method by examining studies published within the last five years (2020–2025) that are relevant to adolescent social interactions in school environments. The findings indicate that peer pressure and conformity significantly influence negative social behaviors, including bullying, verbal aggression, delinquency, and low self-esteem, while positive peer support contributes to enhancing psychological well-being, self-control, and learning motivation. Overall, peer interactions can act as both risk and protective factors in adolescent behavioral development. This review emphasizes the importance of peer-based interventions, psychoeducation, and school counseling programs to create a safe, inclusive, and supportive social environment for junior high school students.